2019
DOI: 10.1111/eci.13173
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in pregnancy causes a volume overload in third trimester

Abstract: Background Obesity is a major risk factor for cardiovascular diseases. In this study, we aimed to investigate the maternal circulatory differences during pregnancy between obese and normal weight women. Materials and methods The functioning of the maternal circulation (arteries, veins, heart and body fluid) was assessed by ECG‐Doppler ultrasound, impedance cardiography (ICG) and bio‐impedance during pregnancy in obese women (BMI ≥30 kg/m2) and normal weight, nonobese women (BMI 20‐25 kg/m2). In this observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…One explanation for this evolution is an endothelial dysfunction triggered by an intravascular overload with a subsequent increase in the vascular tone (peripheral vascular resistance) and a decrease in the cardiac output, as observed in pregnant women with obesity during an uncomplicated third trimester pregnancy. 25 Endothelial dysfunction caused by intravascular volume overload has been documented in nonpregnant individuals during hemodialysis 26 and acute heart failure. 27 For late-onset preeclampsia, frequently seen in women with obesity, high-output circulation is seen throughout all the stages of pregnancy, including the clinical stage of late-onset preeclampsia, during delivery, and postpartum 28 (Figure 2).…”
Section: Expert Review Ajogorgmentioning
confidence: 99%
“…One explanation for this evolution is an endothelial dysfunction triggered by an intravascular overload with a subsequent increase in the vascular tone (peripheral vascular resistance) and a decrease in the cardiac output, as observed in pregnant women with obesity during an uncomplicated third trimester pregnancy. 25 Endothelial dysfunction caused by intravascular volume overload has been documented in nonpregnant individuals during hemodialysis 26 and acute heart failure. 27 For late-onset preeclampsia, frequently seen in women with obesity, high-output circulation is seen throughout all the stages of pregnancy, including the clinical stage of late-onset preeclampsia, during delivery, and postpartum 28 (Figure 2).…”
Section: Expert Review Ajogorgmentioning
confidence: 99%
“…46 This observation is particularly evident in obese women, whose body water volume and cardiac output are constitutionally larger than those of normal-weight women. 47,48 The latter is considered to result from an increased intraabdominal pressure and external renal vein compression, leading to an increased glomerular capillary pressure with the activation of the juxtaglomerular apparatus and the reninAE angiotensinAEaldosterone system with subsequent sodium and water retention. 49 Gestational volume expansion superimposed on the constitutionally high intravascular volume of obese women is associated with a reduction of the cardiac output and an increase in the total vascular resistance during an uncomplicated third trimester pregnancy, an observation untrue for normalweight pregnant women.…”
Section: Gestational Volume Expansion: a Stressor For The Maternal Ca...mentioning
confidence: 99%
“…Studying the mother's body composition and correlating it with her energy balance could facilitate the development of dietary recommendations for women that would help to ensure adequate weight gain dur-ing pregnancy. Obesity is a major risk factor for cardiovascular disease [91]. In the studies by Piuri et al it has been shown that women with hypertensive disorders caused by overweight and obesity had increased TBW and ECW already in early pregnancy [82].…”
Section: Weight Gain In Pregnancy and Gestational Diabetes Mellitusmentioning
confidence: 99%
“…BIA is also used as one of the additional tests in assessing the risk of developing GH and PE [68,69,75,91]. PE is a serious disease diagnosed in 2-8% of pregnancies [98,99], and it is associated with the risk of preterm labour.…”
Section: Gestational Hypertension and Preeclampsiamentioning
confidence: 99%